PENGGUNAAN MODELEVERY ONE IS A TEACHER HERE DENGAN VARIASI CALL ON THE NEXT SPEAKER DALAM MENUMBUHKAN PARTISIPASI SISWA KELAS VII DI MTS AULIA CENDEKIA PALEMBANG - Devara Futry; Nyayu Soraya; Mutia Dewi (Jurnal PAI Raden Fatah, 2022)
This study aims to determine the significant difference in student learning participation tested through the Everyone Is a Teacher Here learning model with variations of Call On The Next Speaker with students who were taught through conventional learning in class VII students of MTs Aulia Cendekia Palembang. This study is an experimental study with a one-group pretest-posttest design. The research population is class VII which is 400 students, from 400 students there are 20 students who are tested. Determination of the sample is done using random sampling. The data collected is the result of student learning activities obtained from the acquisition of questionnaire scores/assessment instruments. The data collected were analyzed using descriptive statistics using the t-test formula. The results of the participating research on students before using the Every Oeverne Is A Teacher Here learning model with variations of Call On The Next Speaker on the students of Al-Quran Hadith material there are 3 categories, which are included in the high category there are 2 students (10%), the medium category is 13 students (65%). In the low category, there are 5 students (25%). Student participation after using the Everyone Is A Teacher Here learning model with variatyoneions of Call On The Next Speaker on the Al-Quran Hadith material students there are 3 categories, which are included in the high category there are 9 students (45%), the medium category is 6 students (30 %. In the low category, there are 5 students (25%). Based on the results of hypothesis testing using the t-test, it shows that the t0 value is 12 and the t-table at a significant level of 5% is 1.68 and at a significant level of 1% is 1.3 so Ha is accepted and Ho is rejected. So it can be concluded that there are differences in student participation using the Everyone Is A Teacher Here learning model with variations of Call On The Next Speaker for students with Al-Quran Hadith material at MTs Aulia Cendekia Palembang.